2012
DOI: 10.1093/eurpub/ckr191
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic correlates of physical activity and physical fitness in German children and adolescents

Abstract: An intervention aiming to improve PA levels, and consequently PF levels, must, with respect to age and gender, refer to SES, as well as immigration background, but not to rural-urban differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 28 publications
7
44
2
3
Order By: Relevance
“…In contrast, children with high SES revealed the smallest amelioration in both tests. In general, children with lower SES background are less physically active (Federico, Falese, & Capelli, 2009), have lower levels of physical fitness (Lammle et al, 2012) and motor skills (Sprague, Kile, Lipscomb, McClelland, & MacDonald, 2013) compared to children with higher SES background. This can be attributed to socio-environmental factors e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, children with high SES revealed the smallest amelioration in both tests. In general, children with lower SES background are less physically active (Federico, Falese, & Capelli, 2009), have lower levels of physical fitness (Lammle et al, 2012) and motor skills (Sprague, Kile, Lipscomb, McClelland, & MacDonald, 2013) compared to children with higher SES background. This can be attributed to socio-environmental factors e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The process of children's motor development is depending on internal and external factors such as family's social-economic status (Mongraw-Chaffin et al) (Lammle, Worth, & Bos, 2012), parent's educational level (Cools, De Martelaer, Samaey, & Andries, 2011), gender (Greendorfer, 1980) and age (Morris, Williams, Atwater, & Wilmore, 1982). But in general without a sufficient degree of movement, the necessary stimuli for the development are missing.…”
Section: Introductionmentioning
confidence: 99%
“…22 Recently, several studies have suggested that families with lower SES have lower levels of physical activity and physical fi tness than those with higher SES. [23][24][25] This is an important fi nding when we consider that physical activity level aff ects the lifetime fi tness and health level.…”
Section: Discussionmentioning
confidence: 99%
“…The development of motor abilities depends on several aspects, such as biological factors like growth and maturity characteristics, and environmental factors, for example, social class affiliation or parental variables [10] [13]. Further, it has been shown that migrant status affects children's activity levels and motor abilities negatively [13].…”
Section: Introductionmentioning
confidence: 99%
“…Further, it has been shown that migrant status affects children's activity levels and motor abilities negatively [13]. A Swedish study showed that children whose parents were born abroad had a higher risk of being less physically active [14].…”
Section: Introductionmentioning
confidence: 99%